Analysis of Sharia Economic Law on the Practice of Party Equipment Rental at 'Aisyiyah Tunas Harapan Orphanage in the Perspective of Sustainable Development Goals (SDGs) - Rahmat; Aiyub Anshori; Mahrus; Yusuf Rohmat Yanuri (Profetika: Jurnal Studi Islam, 2024)
Objective: This study aims to analyze the Sharia Economic Law perspective on the practice of party equipment rental at 'Aisyiyah Tunas Harapan Orphanage and its alignment with the Sustainable Development Goals (SDGs), particularly in promoting economic growth and social welfare. Renting, known in Islam as Ijarah, is a fundamental concept in Sharia economics that serves as an alternative solution for economic empowerment. The 'Aisyiyah Tunas Harapan Orphanage utilizes party equipment rental as a means to support its operational costs and improve economic sustainability. However, there is a lack of awareness among the orphanage managers and the local community regarding the principles of Sharia Economic Law, raising concerns about the compliance of rental agreements with Islamic teachings. Theoretical framework: This research is grounded in the theoretical framework of Ijarah contracts in Islamic jurisprudence, which stipulates that rental agreements must adhere to transparency, mutual consent, and fairness principles. Literature Review: The literature review examines previous studies on Sharia-based rental agreements and their role in economic sustainability. Methods: This study employs qualitative field research with a normative-descriptive approach. Data sources consist of primary data obtained through interviews, observations, and documentation, and secondary data derived from scholarly works on Islamic economic law. The data analysis method follows an interactive model, encompassing data reduction, data display, and conclusion verification. Results: The findings indicate that while the rental mechanism at 'Aisyiyah Tunas Harapan Orphanage functions as an economic support system, there are gaps in contract formulation and compliance with Islamic legal principles. The study suggests that implementing proper Sharia-based rental agreements can enhance financial sustainability and contribute to SDG goals, particularly economic inclusivity and responsible financial practices. Implications: The implications of this study emphasize the need for Sharia-compliant business models within charitable institutions to ensure ethical and sustainable economic activities. Novelty: The novelty of this research lies in integrating Islamic economic law with SDG principles in the context of orphanage-based entrepreneurship.